Recent Advances in Models of Immune-Mediated Drug-Induced Liver Injury - Tasnim, Farah; Huang, Xiaozhong; Lee, Christopher Zhe Wei; Ginhoux, Florent; Yu, Hanry (Frontiers in Toxicology, 2021)
Hepatic inflammation is a key feature of a variety of liver diseases including drug-induced liver injury (DILI), orchestrated by the innate immune response (Kupffer cells, monocytes, neutrophils, dendritic cells) and the adaptive immune system (T cells and natural killer T cells). In contrast to acute DILI, prediction of immune-mediated DILI (im-DILI) has been more challenging due to complex disease pathogenesis, lack of reliable models and limited knowledge of underlying mechanisms. This review summarizes in vivo and in vitro systems that have been used to model im-DILI. In particular, the review focuses on state-of-the-art in vitro human-based multicellular models which have been developed to supplement the use of in vivo models due to interspecies variation and increasing ethical concerns regarding animal use. Advantages of the co-cultures in maintaining hepatocyte functions and importantly, introducing heterotypic cell-cell interactions to mimic inflammatory hepatic microenvironment are discussed. Challenges regarding cell source and incorporation of different cells with physical cell-cell contact are outlined and potential solutions are proposed. It is likely that better understanding of the interplay of immune cells in liver models will allow for the development of more accurate systems to better predict hepatotoxicity and stratification of drugs that can cause immune-mediated effects.